A estetização da alma pelo corpo no Fédon de Platão. - Araújo, Hugo Filgueiras de (2012)
This thesis proposes a reading of the Phaedo, Plato, centered on the theme of the body / soul that permeates all arguments of the dialogue. Plato in his writings announces care for the soul, and consider it a source of knowledge and virtue, and even the "self" of man. The care and appreciation of the soul are so essential to Plato that in some parts of the Phaedo the philosopher, to relate it to the body, considered as a kind of prison for obstacle and understand that wisdom is sought by those who dedicated to philosophy, is beyond the sensitivity (aísthesis), and while the body is united, the soul will not reach the truth in its fullness. Being part of the body sensitive instance, the philosopher sets before him in an attitude of mistrust, but must admit that at other times by Plato believes that it (the body) and that it begins the search for truth, set by reminiscence thus acknowledging its role. This paper conducts a study on the body / soul considering that it is possible to establish a unified reading of the different ways in which it is presented from an aesthetic dimension: Plato speaks about the care that must be taken in dealing with the body because soul influenced the associated sensitivity that even imposing obstacles to knowledge is the means and instrument through the senses, so you can be learning about things. During the argument, some problems will be solved, because declare that the soul, in order of Forms immutable, can suffer change seems to be strange. The impasse is solved with the help of other dialogues: Republic, Phaedrus and Timaeus, who understand the soul as a reality of a mixed nature, being a metaxú, an intermediate between the divisible and indivisible, the Other and the Same, the mutable and immutable . Finally, the thesis incur the assertion that Plato in the Phaedo is proposing a project that teaches men to practice self-control.